Interventions to improve the rate or timing of initiation of antiretroviral therapy for HIV in sub-Saharan Africa: meta-analyses of effectiveness - Fox, Matthew P.; Rosen, Sydney; Geldsetzer, Pascal; Bärnighausen, Till; Negussie, Eyerusalem; Beanland, Rachel (Journal of the International AIDS Society, 2016)
Introduction As global policy evolves toward initiating lifelong antiretroviral therapy (ART) regardless of CD4 count, initiating individuals newly diagnosed with HIV on ART as efficiently as possible will become increasingly important. To inform progress, we conducted a systematic review of pre-ART interventions aiming to increase ART initiation in sub-Saharan Africa. Methods We searched PubMed, Embase and the ISI Web of Knowledge from 1 January 2008 to 1 March 2015, extended in PubMed to 25 May 2016, for English language publications pertaining to any country in sub-Saharan Africa and reporting on general adult populations. We included studies describing interventions aimed at increasing linkage to HIV care, retention in pre-ART or uptake of ART, which reported ART initiation as an outcome. We synthesized the evidence on causal intervention effects in meta-analysis of studies belonging to distinct intervention categories. Results and discussion We identified 22 studies, which evaluated 25 interventions and included data on 45,393 individual patients. Twelve of twenty-two studies were observational. Rapid/point-of-care (POC) CD4 count technology (seven interventions) (relative risk, RR: 1.26; 95% confidence interval, CI: 1.02-1.55), interventions within home-based testing (two interventions) (RR: 2.00; 95% CI: 1.36-2.92), improved clinic operations (three interventions) (RR: 1.36; 95% CI: 1.25-1.48) and a package of patient-directed services (three interventions) (RR: 1.54; 95% CI: 1.20-1.97) were all associated with increased ART initiation as was HIV/TB service integration (three interventions) (RR: 2.05; 95% CI: 0.59-7.09) but with high imprecision. Provider-initiated testing (three interventions) was associated with reduced ART initiation (RR: 0.91; 95% CI: 0.86-0.97). Counselling and support interventions (two interventions) (RR 1.08; 95% CI: 0.94-1.26) had no impact on ART initiation. Overall, the evidence was graded as low or moderate quality using the GRADE criteria. Conclusions The literature on interventions to increase uptake of ART is limited and of mixed quality. POC CD4 count and improving clinic operations show promise. More implementation research and evaluation is needed to identify how best to offer treatment initiation in a manner that is both efficient for service providers and effective for patients without jeopardizing treatment outcomes.
Gesehen am 03.06.2020